(3RHOI GdWHs - (3ESeGYjd Hf MSjf GdMSjfj, CHh EHQGgje, Rjf GdOjf GdLQLGfj,J (B531 (3g` s ((3MSjf Hf GdMSf Hf GdeDjO Gdhai s)
(3ChdgG (B:s
(3CeG HYO MeOkG ddg SHMGfg hGdKfGA Ydjg aCYde Cf eHfi GdWH Ydi eYQaI MGdi HOf GdGfSGf ef GdUMI hGdeQV GdHGH GdChd ai MO GdfHU heYQaI CLfGSI s
(3BNQgG (B:s
(3gOGjI bGdhG EPG CQOfG Cf fYde Cf GdbeQ ai Ci HQL GdeSJbje jchf YOO OQL GdbeQ ai Pdc hHg fNJe GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B308s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B952s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs